Description and impact of neuroscience advances on the development of artificial intelligence (2024)
The development of the research allows the descriptive writing of this article, this writing is the result of a research conducted to twentyfive respondents with teaching training in the field of education at undergraduate and graduate level in Colombia and Spain, all the actors involved participated voluntarily, where they gave express and clear authorization for the treatment and use of the answers in the forms, The purpose of this research is to describe in an exhaustive way the incidence of the advances in neuroscience in the development of artificial intelligence, this research has a quantitative approach, which is oriented to describe the incidence of Neuroeducation in front of the reality of AI for the education of the XXI century, in which determines own characteristics and own steps of the research, where Hernandez et al, (2014) states that data collection occurs in natural and participatory scenarios, using the survey as the main instrument for data collection, finally, and as a result it is defined that neuroscience makes a significant contribution to the improvement of AI digital tools in education, since it allows understanding the learning processes, designing friendly and appropriate interfaces according to the content with human cognition, are arguments that respondents consider important, with a social, mental and positive representation in various aspects, from the condition of preparation, instruction and even safety and ethics in the use of AI, Corvalán, (2018).